Limited Offline Learning Methods For Mathematics With Collected Materials In Junior High School Students - Umul Khayati (Journal of Education and Learning Mathematics Research (JELMaR), 2021)
Abstract: This study describes the learning that has been applied in MTs students to the set material during the New Normal Covid-19 period. The learning method used is the Discovery learning method which is expected to improve the reciprocal relationship between students and teachers. In addition, the learning used was limited offline which paid attention to health protocols such as wearing masks, spraying hand sanitizers, and spraying disinfectants before students entered the school area and checking body temperature. Limited offline learning is different from learning before the Covid-19 pandemic existed, offline learning is limited to face-to-face learning between teachers and students but reduces face-to-face hours, namely 08.00-10.00 WIB. This limited offline learning is implemented because students do not allow learning to be carried out online because of the many obstacles faced by students, teachers, and parents of students. The results of the study indicate that there are differences in the conditions of students when this limited offline learning is implemented. In this case, limited offline learning has positive and negative effects for both teachers and students.